Energy efficiency, market competition, and quality certification: Lessons from Central Asia. (June 2023) - Otrachshenko, Vladimir; Hartwell, Christopher A.; Popova, Olga
Abstract: Energy efficiency at the firm level is determined by a series of complex and multifaceted factors related to firm-specific attributes and a firm's external environment. A weak institutional environment may exacerbate barriers to energy efficiency, sending interested firms in search of ways in which to signal their commitment to improving their energy usage. Paramount among these mechanisms is internationally recognized quality certification, which can both reward a firm for prior improvements and alert consumers about the quality of a firm's products. This paper examines the effect of quality certification on energy efficiency in a particularly low institutional quality environment, the four transition countries of Central Asia. Using firm-level data and controlling for other determinants of energy intensity, we find that firms that have quality certifications are indeed more efficient in their use of energy. Perhaps more importantly, we find that competition from the informal sector is also incredibly important to improved energy efficiency. The effect of certification also runs back to firm planning, as certified firms are more likely to focus on energy efficiency metrics rather than overall usage in planning for the future. Highlights: Central Asia is an important player in global energy markets. Quality certification in Central Asia leads to firms being more energy efficient. A similar impact on energy efficiency is found because of informal competition. Firms that make personnel changes in favor of efficiency show better results.